Emotional instability and expressive suppression are related to paranoia in daily life: An electronic mobile assessment study in nonclinical individuals. Issue 3 (18th September 2019) - Nittel, Clara Marie; Lamster, Fabian; Rief, Winfried; Kircher, Tilo; Soll, Daniel; Mehl, Stephanie
: Although instable negative emotions and problems in emotion regulation (ER) are common in patients with psychosis and are discussed as potential factors involved in the formation and maintenance of paranoia, it is unclear whether they increase the risk of developing paranoia in nonclinical controls. The present study aims to investigate whether the instability of negative emotions leads to paranoia in healthy participants. It should be further analyzed if the application of maladaptive ER strategies enhances subclinical paranoid ideation and if the use of adaptive ER strategies reduces subclinical paranoid ideation. Method: Nonclinical controls ( n = 83) repeatedly reported the presence and instability of negative emotions, paranoia, and the use of maladaptive (expressive suppression, rumination) and adaptive (reappraisal, acceptance) ER strategies in their daily life on six consecutive days using electronic mobile assessment. Results: Hierarchical linear regression analysis revealed that nonclinical controls reporting a pronounced instability of negative emotions showed more pronounced paranoia at a subsequent time point. Moreover, participants who used expressive suppression at a certain time experienced more severe paranoia at the subsequent time point. Conclusion: If these findings are confirmed in high-risk samples, ER processes could be considered as an additional factor in theoretical models of paranoia formation.